The Application of Storytelling Techniques for Increasing Speaking Interest in Children with Speech Delay at TK Santhi Yasa Kumara Gianyar - Raka Pratami, Dewa Ayu; Surya Wahyuni, Ida Ayu Ketut (International Journal of Multidisciplinary Sciences, 2024)
The purpose of this study is to investigate how storytelling techniques can be used to help children with speech delays at TK Santhi Yasa Kumara in Gianyar improve their speech abilities. Speech delay is a common issue affecting children's communication development, often leading to difficulties in social interactions, academic performance, and overall language acquisition. The study aims to explore how storytelling can be integrated into early childhood education practices to address this issue. The research employs a qualitative phenomenological approach to gain in-depth insights into the experiences of children, teachers, and parents in using storytelling to improve speech development. Data was collected through direct observations of storytelling sessions, semi-structured interviews with teachers and parents, and analysis of curriculum documents. Storytelling was chosen due to its potential to engage children, promote active listening, and encourage verbal expression through interactive narratives. The findings indicate that storytelling techniques, when used consistently and with strong support from both families and the school community, significantly enhance the speech abilities of children with speech delays. Specifically, children showed improvements in vocabulary, sentence structure, and overall communication skills. The research concludes that storytelling is an effective tool for supporting children with speech delays, and recommends its integration into daily teaching practices, with ongoing involvement from families, to maximize its impact on speech development.